Answer :
Answer:
J ) j = - 3,
K ) h = 9,
M ) d = - 24,
N ) x = 1 / 2
Step-by-step explanation:
J )
[tex]4(1-2j) = 7(2j + 10),\\4-8j=14j+70,\\-8j=14j+66,\\\\-22j=66,\\j = - 3,\\\\Solution, j = - 3[/tex]
I applied the distributive property, resulting in the second step. Afterwards I subtracted 4 from either side of the equation, received - 22j = 66 after combining like terms, and divided - 22 on either side to get j = -3.
K )
[tex]4 / 3h = 12,\\4h = 36,\\h = 36 / 4 = 9\\\\Solution, h = 9[/tex]
Multiplying each end of the equation by 3 resulted in the simplified expression 4h = 36. Dividing either side by 4, I got h = 9.
M )
[tex]d / 4 - d / 3 = 2,\\3d - 4d = 24,\\- d = 24,\\\\Solution, d = - 24[/tex]
Taking the LCM of 4 and 3, I got 12, multiplying either side by 12 / 12. Combining like terms and dividing - 1 on either side of the equation - d = 24, I received d = - 24.
N )
[tex]7 = - 2 * ( - 3 - x ),\\- 3 - x = - 7 / 2,\\- x = - 1 / 2,\\\\Solution, x = 1 / 2[/tex]
After dividing the first equation by - 2 on each end, I received a simplified equation that, by adding 3 on it's part, got x to be = 1 / 2